Antecedents and Consequences of Economic Growth in ASEAN Countries - Imleesh, Mohammed Mahmoud Mohammed; Arief, Sandy; Rozi, Fahrur (Universitas Negeri Semarang, 2025)
Association of Southeast Asian Nations (ASEAN) standing out as the most developed intergovernmental institution. ASEAN countries have demonstrated impressive economic growth average annual growth rate of 4.2% over the past decade. This study investigates the impact of key macroeconomic variables Foreign Direct Investment (FDI), inflation, unemployment, exchange rate, and green trade on economic growth in ten ASEAN member states. Additionally, it examines the mediating role of FDI in shaping these relationships. Employing panel data regression over a 15-year period (2008–2022), the analysis reveals a significant negative correlation between inflation and economic growth, reflecting the detrimental effects of price instability on economic activity. In contrast, unemployment, exchange rate, and green trade exhibit positive correlations with growth, suggesting that higher employment levels, currency stability, and environmentally sustainable trade practices bolster economic performance. FDI plays a critical mediating role by injecting capital and advanced technology, thereby enhancing productivity, innovation, and job creation. The study underscores the necessity of integrated economic policies that simultaneously address inflation, employment, exchange rate management, and green trade promotion, while actively fostering FDI to support sustainable and resilient economic development across the ASEAN region.